2021
DOI: 10.1016/j.jtbi.2020.110501
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the number of reported and unreported cases for the COVID-19 epidemics in China, South Korea, Italy, France, Germany and United Kingdom

Abstract: Highlights corona virus, reported and unreported cases, isolation, quarantine, public closings; epidemic mathematical model

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 20 publications
1
93
0
Order By: Relevance
“…In this article, we proposed a new epidemic model involving the daily number of tests as an input of the model. The model itself extends our previous models presented in ( Griette et al., 2020 ; Liu et al., 2020a , 2020b , 2020c , 2020d , 2021 ). We proposed a new method to use the data in such a context based on the fact that the cumulative number of tests grows linearly at the early stage of the epidemic.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this article, we proposed a new epidemic model involving the daily number of tests as an input of the model. The model itself extends our previous models presented in ( Griette et al., 2020 ; Liu et al., 2020a , 2020b , 2020c , 2020d , 2021 ). We proposed a new method to use the data in such a context based on the fact that the cumulative number of tests grows linearly at the early stage of the epidemic.…”
Section: Discussionmentioning
confidence: 57%
“…More recently the method was extended and successfully applied to a Japanese age-structured dataset in ( Griette et al., 2020 ). The method was also extended to investigate the predictability of the outbreak in several countries including China, South Korea, Italy, France, Germany and the United Kingdom in ( Liu et al., 2021 ). The application of the Bayesian method was also considered in ( Cotta et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…When transformed to the basic reproduction number R 0 , the differences across the countries were more obvious. Fixing the fraction of asymptomatic infectious that become reported symptomatic infectious at 0.6, Magal et al utilized a similar modified SEIR model and reported basic reproduction number R 0 to be 3.79, 4.21 and 4.45 for Italy, Germany, and France, respectively [ 27 ]. It seemed that our estimates of R 0 are close to their results.…”
Section: Discussionmentioning
confidence: 99%
“…More recently the method was extended and successfully applied to a Japanese age-structured dataset in [11]. The method was also extended to investigate the predictability of the outbreak in several countries China, South Korea, Italy, France, Germany and the United Kingdom in [18]. The application of the Bayesian method was also considered in [9].…”
Section: Introductionmentioning
confidence: 99%